MODELLING THE CAUSES OF TAX DEFAULT AMONG SMALL AND MEDIUM SCALE ENTERPRISES (SMEs) IN THE TAMALE METROPOLIS OF GHANA - Seidu, Ali Napari; Abdul, Iddrisu Wahab; Sebil, Charles (European Scientific Journal, ESJ, 2015)
The study examined the factors that have a higher potential for tax default among Small and Medium Scale Enterprises (SMEs) such as high tax rates on SMEs with their relatively low income levels, complex tax filing procedures, lack of proper tax education, high illiteracy rate among SMEs, Poor record keeping, multiple taxation and under declaration of income. The logistic regression model was used in this study to estimate the effect of the statistically significant factors on tax default. The findings revealed that the three most significant factors accounting for tax default among SMEs are the kind of SMEs, inadequate tax education by tax authorities, and multiple taxation. It is therefore recommended that SMEs should be adequately educated on the importance of tax to the state and be encouraged to pay tax to IRS and other mandatory agencies for the development of the Nation. Government as a policy should make tax payment attractive and unavoidable by both the informal and formal sectors.